2019
DOI: 10.1007/s40195-019-00931-1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Stress Rupture Properties of a 3rd-Generation Nickel-Based Single-Crystal Superalloy at 1100 °C/150 MPa

Abstract: The influence of orientation on the stress rupture behaviors of a 3rd-generation nickel-based single-crystal superalloy was investigated at 1100 °C/150 MPa. It is found that the stress rupture anisotropy is shown at 1100 °C, but not so obvious compared with that at intermediate temperatures. The [001] specimens display the longest rupture life, [111] specimens show the shortest rupture life, and [011] specimens exhibit the intermediate life. Detailed observations show that the final fracture is caused by crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The results agree with the morphology of the fracture surface defined in the work of Ranieri that assess the behavior of plasma nitrided 4340 Steel [37]. In plasma nitrocarburizing coating work on AISI 4340 steel, performed by Li et al, the creep failure morphology showed a similar aspect with microcavities and ductile fracture, both in coated and uncoated conditions [38]. The coated specimens show good adhesion to almost the entire perimeter of the sample under conditions of 200 and 250 MPa, with partial detachment in some areas.…”
Section: Fractographic Analysissupporting
confidence: 86%
“…The results agree with the morphology of the fracture surface defined in the work of Ranieri that assess the behavior of plasma nitrided 4340 Steel [37]. In plasma nitrocarburizing coating work on AISI 4340 steel, performed by Li et al, the creep failure morphology showed a similar aspect with microcavities and ductile fracture, both in coated and uncoated conditions [38]. The coated specimens show good adhesion to almost the entire perimeter of the sample under conditions of 200 and 250 MPa, with partial detachment in some areas.…”
Section: Fractographic Analysissupporting
confidence: 86%
“…Therefore, Ni-based single-crystal superalloys with excellent high-temperature performance are widely used in the manufacturing of turbine blades. 1,2 However, in the actual operational process of turbine blades, relying solely on the material's temperaturebearing capacity falls far short of meeting the extreme temperature requirements. According to statistics, the improvement of high-temperature alloys and their manufacturing processes only contributes 30% to the increase in inlet temperature, while the other 70% benefits from the improvement of cooling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…As the core component of the aircraft engine, the high‐temperature bearing capacity of the turbine blade is a key factor that restricts the increase in inlet temperature. Therefore, Ni‐based single‐crystal superalloys with excellent high‐temperature performance are widely used in the manufacturing of turbine blades 1,2 . However, in the actual operational process of turbine blades, relying solely on the material's temperature‐bearing capacity falls far short of meeting the extreme temperature requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have proved that a lower vacuum pressure, a larger snorkels sectional area, [24,37] a deeper immersion depth, [14,38] and bottom blowing [13,16] would favor to optimize the fluid flow in RH. Recently, some researchers have tried to improve the refining efficiency by using single-leg, [28,34] some multi-legs [9,15,39,40] snorkel and magnetic field [30,41] surround the snorkels. However, the multileg and the rotating magnetic field were hardly used some time in the actual industrial manufacture considering the cost issue.…”
Section: Introductionmentioning
confidence: 99%